Unraveling the Cultural Dynamics of Nonviolence in Schools: A Study of the Development of Nonviolence Pedagogy - Manuardi, Ardian Renata (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Violence in educational settings remains a critical issue that causes psychological trauma, perpetuates intergenerational cycles of aggression, and undermines the role of schools as safe spaces for students. This study aims to explore the cultural dynamics of nonviolence in schools through conceptual analysis, bibliometric review, and a quantitative survey. The adapted Teenage Nonviolence Test (TNT) for Indonesian adolescents was employed, measuring four key dimensions: Physical Nonviolence, Psychological Nonviolence, Satyagraha, and Tapasya. Data were collected from junior high school students from both conventional schools and Islamic boarding schools, analyzed using descriptive-analytic methods, one-way ANOVA, and supported by qualitative insights. The findings indicate that the culture of nonviolence in schools remains underdeveloped and is strongly influenced by protective factors within families and communities. Bibliometric analysis further revealed that nonviolence research over the past decade has been dominated by philosophical, legal, and political perspectives, while counseling and psychology remain underexplored. This study highlights the need for a systemic approach to foster a safe, inclusive educational environment grounded in nonviolent values, positioning nonviolence not only as a strategy to prevent harm but also as a pathway to positive peace and social justice.